سياقية الأحاديث عن الجهاد والحرب: دراسة براغماتية وسوسيولوجية في تفسير أخلاقيات العنف في الإسلام - Gita Putri Ramadhani; Mad Ali (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2025)
Discourse on jihad in hadith studies often becomes distorted due to the separation of texts from their historical and pragmatic contexts, which in turn leads to the legitimation of violence and the rise of religious militancy. This study develops an integrated analytical model to restore the meaning of jihad within the framework of propheticethics and communication. By combining a pragmatic speech-act approach with Berger and Luckmann’s social construction theory, this analytical framework links the communicative functions of the Prophet’s sayings—including illocutionary types, linguistic conditions, implicatures, asbāb al-wurūd, and the context of defensivewarfare—with the social construction of hadith meaning through externalization, objectivation, and internalization. Three key hadiths are examined: umirtu an uqātila an-nās, al-harb khud‘ah, and the prohibition against killing women and children. Findings reveal their directive-defensive, representative–commissive, and normative declarative characteristics, which affirm Islamic ethics of warfare. Sociologically, the three hadiths construct a rational, ethical, and humanistic understanding of jihad. In the digital era, literalist reception often ignores historical and communicative contexts, making contextual hadith literacy increasingly urgent. This study offers humanistic warethics principles and recommends expanding cross-madhhab hadith studies as well asdigital reception research for Islamic education and deradicalization initiatives.